1986
DOI: 10.1111/j.1365-3180.1986.tb00726.x
|View full text |Cite
|
Sign up to set email alerts
|

Distribution of diclofop‐methyl and metabolites in oat (Avena sativa L.) protoplasts

Abstract: The metabolism of the herbicide diclofop-methyl and the distribution of it and its metabolites have been investigated in a system utilizing isolated oat protoplasts {Avena sativa L. 'Cascade')-Accumulations of '''C-diclofop-methyl were found in membrane fractions of the protoplasts. Diclofopmethyl partitioned into the lipid phase of the protoplast plasma membrane. Comparatively small amounts of diclofop were found associated with the protoplasts. Diclofop-methyl was converted to diclofop in the treatment solut… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
2
0

Year Published

1988
1988
2006
2006

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(3 citation statements)
references
References 11 publications
1
2
0
Order By: Relevance
“…uptake and distribution within the plant) [1][2][3][4][5][6], their freeacid forms seem to represent the actual active ingredient. In fact, for some diphenoxy-propionic acid type herbicides it was shown that the applied esters are fast hydrolyzed within the plant cell to the free acids [33]. Similar results as described here for Avena chloroplasts, were also found for diclofop and fenoxaprop using maize chloroplasts [10].…”
Section: Discussionsupporting
confidence: 82%
“…uptake and distribution within the plant) [1][2][3][4][5][6], their freeacid forms seem to represent the actual active ingredient. In fact, for some diphenoxy-propionic acid type herbicides it was shown that the applied esters are fast hydrolyzed within the plant cell to the free acids [33]. Similar results as described here for Avena chloroplasts, were also found for diclofop and fenoxaprop using maize chloroplasts [10].…”
Section: Discussionsupporting
confidence: 82%
“…The aryloxyphenoxypropionates are applied as esters but are rapidly converted to the active acid form of the herbicide (21,30). This esterification reaction presumably oc curs extracellularly (33). Following movement across the cell membrane, the graminicides are translocated to the meristematic regions.…”
Section: Mechanism Of Action Of the Graminicidesmentioning
confidence: 99%
“…Esterase activities toward the herbicides were significantly higher in the weeds than in wheat, most markedly with the AOPP herbicide diclofop-methyl. The respective enzymes have been shown to be expressed in the apoplast in both wild oat (Holl et al, 1986) and wheat (Haslam et al, 2001) and have recently been identified and cloned from black-grass (Cummins and Edwards, 2004). Based on sequence analysis, the 40 kDa esterase from black-grass showed homology to a large group of ill-characterised hydrolases found in micro-organisms and plants termed the GDSL lipases (Brick et al, 1995).…”
Section: Introductionmentioning
confidence: 99%